Analysis of the Object of Tourist Attraction (ODTW) of the Puncak Sekawan Area of Blitar Regency in Terms of Interest in Visiting Tourists: English - Maulana, Feri Fahrian; Wahyudi, Adip; Nurhidayati, Eka; Santika, Indria Dwi; Qonita, Indy (Graduate School, Universitas Brawijaya, 2025)
This study examines the Sekawan Peak tourist attraction in Blitar Regency, focusing on visitor interest based on the Tourist Attraction Object (ODTW) guide. This research aims to evaluate the potential of tourist sites based on indicators of tourist attraction, accessibility, and visitor interest. This study employed a mixed-methods approach to collect primary data through surveys and interviews with 50 participants. The findings show that visitor appeal scored an average of 84%, classified as very feasible, while accessibility reached a score of 66.32%, classified as feasible. Visitor interest reached 84%, indicating a high level of appeal. This study demonstrates that Puncak Sekawan has considerable potential as a leading tourist destination, supported by its natural beauty, improved accessibility, and attractive facilities. Future advice recommends improving infrastructure, expanding tourism facilities, and efficient marketing tactics to increase the number of visitors while maintaining sustainable tourism management to protect the natural environment and local culture.